How to Effectively Display Sponsorship Information: The Influences of External Time Cues and Information Type on Individuals’ Evaluations - Zhang, Yuan (Frontiers in Psychology, 2022)
Time, an important, yet scarce resource in daily living, affects cognition, decision-making, and behavior in various ways. For instance, in marketing practice, time-bound strategies are often employed to influence consumer behavior. Thus, understanding and mastering a target market from a temporal perspective can contribute to the ease with which marketers and businesses formulate marketing strategies. Accordingly, this research conducts three studies to explore the influence of temporal framing as an external time cue on the evaluation of sponsorship-linked marketing campaigns. The studies show that future-framed participants adopted a global processing style. In this context, providing information about the sponsoring brand and sponsored event induced a more positive evaluation of future campaigns. However, in a past-frame context, participants were less likely to adopt a global processing style. Here, providing brand sponsor information alone increased the likelihood of a positive evaluation of past campaigns. Ultimately, the findings provide a theoretical basis for decision-making utilizing the influence of activities and events to enhance brand image.